PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - -, Nurmi; Fitrianti, Nur (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This research aims to examine the impact of financial performance on profit growth in companies listed on the LQ45 index of the indonesia Stock Exchange (IDX) for the period of 2021-2023. Financial performance is assessed using Return on Assets (ROA) as a measure of profitability and Current Ratio (CR) as a measure of liquidity. A quantitative methodology utilizing panel data regression analysis was applied to 28 companies selected based on specific criteria. The findings indicate that neither ROA nor CR significantly affects profit growth, as evidenced by the p-values for both variables exceeding the 0.05 significante thereshold. Additionaly, the very low coefficient of determination (R²) of 0.0049 suggests that these two independent variables are not effective predictors of profit growth variability. These results imply that factors other than profitability and liquidity may exert a more substantial influence on profit growth. This study is anticipated to enhance the field of financial management and provide a valuable reference for investment decision-making and thorough evaluations of company performance.